Pengaruh Kinerja Lingkungan Dan Kinerja Keuangan Terhadap Nilai Perusahaan: (STUDI EMPIRIS PADA PERUSAHAAN CONSUMER NON-CYCLICALS YANG TERDAFTAR PADA BURSA EFEK INDONESIA) - Vianty Adella Santo; Laura Silvany Hivianto (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
Company value is a form of maximum corporate goals through increasing the prosperity of investors. The company value is seen from the price of the stock where the higher the value of the stock, the higher the value of the company. The company value is also known as one of factor for investors in making investments. Therefore, company management must pay attention to the company's value. This research aims to examine the influence of environmental performance and financial performance on firm value. The population in this study is consumer non-cyclicals companies listed on the Indonesia Stock Exchange from 2018 to 2021. Environmental performance is measured by the PROPER rating and financial performance is measured by ROA and DAR. The data obtained are secondary data using purposive sampling method, with a total of 83 observations. This research uses SPSS 25 program with multiple regression statistical analysis model. The results show that environmental performance has a negative effect on firm value. ROA and DAR have a positive effect on firm value.